Answer:
B. Add the two equations.
Explanation:
Lets solve our system of equations step-by-step
Step 1. Add the two equations
2x – 2y = 5 +
5x + 2y = 9
----------------
7x = 14
Step 2. Solve for x in the resulting equation
7x = 14
![x=(14)/(7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hx72a83ymmo0fj9z5wujftkfhmyjek1cnv.png)
x = 2
Step 3. Replace the value of x in any of the original equations
2x – 2y = 5
2(2) – 2y = 5
4 – 2y = 5
-2y = 5 - 4
-2y = 1
![y=-(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rltwn6tix9raldsncebfvof0fdc1yyqv9z.png)
We can conclude that the correct answer is: B. Add the two equations.